Survey on tuberculosis teaching in Brazilian nursing schools, 2004 - Villa, Tereza C. S.; Ruffino-Netto, A.; Andrade, R. L. P.; Alarcón, E. A.; Montero, C. V.; Firmino, D. R. (My University, 2006)
OBJECTIVE: To characterise tuberculosis (TB) teaching in Brazilian nursing schools by state and region and its theoretical and practical contents. METHODOLOGY: In an educational research survey in 2004, 347 nursing schools were identified. Questionnaires were posted to faculties providing training in TB. Data were compiled in a database with a view to descriptive result analysis. Replies to the questionnaire were received by 32% of the nursing schools contacted. RESULTS: Undergraduate TB teaching is heterogeneous. For training in theory, the principle teaching method is through classes in 102 (91.9%) nursing schools. Practical TB teaching is carried out at the primary care level (89.2%). Teachers update their knowledge through events and internet; little reference is made to manuals. The time devoted to practical TB teaching ranges from 10 to 20 hours, although this is not always included in student training. CONCLUSION: Teaching in TB should go beyond the traditional model that focuses only on biological aspects. It should introduce tools that lead to permanent behavioural change, such as a more human approach and social and psychological aspects, such as living conditions, habits and customs. It should involve new partners, such as families, communities and other health professionals, and identify obstacles within the university. © 2006 The Union.
Keywords: Nursing schools; Teaching; Tuberculosis; Brazil; cultural factor; education program; health education; health survey; human; lung tuberculosis; nursing education; primary medical care; priority journal; psychological aspect; review; social aspect; Education, Nursing; Humans; Questionnaires; Retrospective Studies; Schools, Nursing